Comorbidity of Auditory Processing, Attention, and Memory in Children With Word Reading Difficulties - Gokula, Rakshita; Sharma, Mridula; Cupples, Linda; Valderrama, Joaquin T. (Frontiers in Psychology, 2019)
Objectives: To estimate the auditory processing, visual attention, digit memory, and receptive language abilities of children with identified word reading difficulties. Design: Twenty-five children with word reading difficulties and 28 control children with good reading skills participated. All the children were aged between 8 and 11 years, with normal hearing sensitivity and typical non-verbal intelligence. Both groups of children completed a test battery designed to assess their auditory processing, visual attention, digit memory, phonological processing, and receptive language. Results: When compared to children who were good readers, children with word reading difficulties obtained significantly lower average scores on tests of auditory processing, including the frequency pattern test, gaps in noise, frequency discrimination, Dichotic Digit difference Test, and Listening in Spatialized Noise. The two groups did not differ on the discrimination measures of sinusoidal amplitude modulation or iterated rippled noise. The results from children with word reading difficulties showed that 5 children (20%) had comorbid deficits in auditory processing, visual attention, and backward digit memory; whereas 12 children (48%) had comorbid auditory processing and visual attention deficits only, and 2 children (8%) had comorbid auditory processing and digit memory; the remaining children had only auditory processing, visual attention, or digit memory deficits. Conclusion: The current study highlights the general co-existence of auditory processing, memory, and visual attention deficits in children with word reading difficulties. It is also noteworthy, however, that only one-fifth of the current cohort had deficits across all measured tasks. Hence, our results also show the significant individual variability inherent in children with word reading difficulties.